The passage : a novel - Cronin, Justin (Cronin, Justin. Passage trilogy., 2010)
A security breach at a secret U.S. government facility unleashes the monstrous product of a chilling military experiment that only six-year-old orphan Amy Harper Bellafonte can stop.